Monopolistic Market Position and Losses from Monetary Integration - Paweł Młodkowski (Contemporary Economics)
The objective of the paper is to show how a market position influences company’s gains and losses from monetary integration. The literature on monetary integration already features cost and benefit analysis. However the proposed examples of both results (negative and positive) are not offered for different market structures and most often are macroeconomic in nature. The paper develops an idea that a monopolistic enterprise might be worse off because of monetary integration. The case discussed, shows that prior to monetary integration, a specific solution regarding pricing of imported goods allowed the company for: (1) hedging effectively from exchange rate risk, (2) benefiting from long-term appreciation trend of the domestic currency against the euro. Both goals were achieved due to privileged market position (legal monopoly) of the company. The monetary integration and the expected full EMU accession is going to remove the need for hedging but simultaneously it will result in loosing the ability to achieve extra profits extracted so far. This is a basis for a claim that costs and benefits flowing from monetary integration could depend on market structure an entity operates in. We conclude that in a more monopolized economies, the microeconomic benefits achieved by households are at the cost of firms, while in a perfect competition gains are uniformly distributed across agents at supply and demand sides of markets. Therefore, producers in monopolized economies could be less prone to join a monetary union. The opposite hypothesis might also be true. In economies with fewer monopolies there are fewer incentives to oppose monetary integration. The comparison of the two extreme settings allows posting a hypothesis that the perfect competition is monetary integration-neutral and the monopoly is monetary integration-averse market structure. Data for the paper and the studied case are originating from one of the largest legal monopolists in Poland that utilizes privileged market position. Despite the mechanism discussed is a real-life one, the particular numbers are adjusted to protect company-specific solutions.